Mexico : Financial System Stability Assessment Update, including Summary Assessments on the Observance of Financial Sector Standards and Codes on the following topics; The Basel Core Principles for Effective Banking Supervision, and the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
Policies implemented over the last decade have strengthened economic fundamentals and brought macroeconomic stability. Major improvements in compliance with the Basel Core Principles for Effective Banking Supervision and the implementation of International Organization of Securities Commission Principles and Objectives of Securities Regulation have been taken up. Significant progress regarding the banking safety net and evaluation of antimoney laundering practices in Mexico are under way. The key remaining challenges are to further entrench stability and to promote wider and more efficient private sector access to financing.